QĪMATU ḤUBBIL WAṬAN FĪ SYI’RI “LIBYA JINĀḤU AL-‘URŪBBAH” LI ‘ALI ṢIDQĪ ‘ABDUL QĀDIR - Alam An Shori; Laily Fitriani; Nur Hasaniyah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Research on Arabic literature in Libya, especially on literature in the nationalist genre, is important to study to examine the correlation between the values of nationalism or what is commonly referred to as Pan Arabism, which Muammar Gaddafi championed, and the Libyan Arabic poetry that developed at that time. Researchers are interested in analyzing the value of love for one's country in the poem